Effect of L21 and XA ordering on structural, martensitic, electronic, magnetic, elastic, thermal and thermoelectric properties of Co2FeGe Heusler alloys. (1st November 2022) - Raïâ, M.Y.; Masrour, R.; Hamedoun, M.; Kharbach, J.; Rezzouk, A.; Hourmatallah, A.; Benzakour, N.; Bouslykhane, K.
Abstract: Based on density functional theory (DFT), the structural, martensitic transition, band structure, density of states, elastic, magnetic, and thermoelectric properties of L21 and XA ordering of Co2 FeGe compound were investigated. The calculated total energy shows that the most stable phase of these compounds is the L21 type with ferromagnetic state using GGA + U approach. In addition, the possible martensitic transition is occurring for L21 phase which has minimum energy localized at c/a = 1.02. The electronic density of states (DOS) and band structure of Co2 FeGe exhibit a ferromagnetic metallic for both L21 and XA phases. From the calculated elastic constants show that the studied phases are elastically anisotropic and satisfies Born′s criteria for mechanical stability. Moreover, through the quasi-harmonic Debye model applied in the Gibbs codeand the thermodynamic analyses have also been estimated. Also, the thermoelectric properties for the both L21 and XA structures are examined and discussed based on the Seebeck, electrical conductivity and thermal conductivity coefficients. Highlights: FPCs based on GGA(+U) were used to study the magnetoelectronic, elastic, thermal and thermoelectric properties of Co2 FeGe. Lattice parameter and bulk modulus of Co2 FeGe was computed and is agrees with experimental and theoretical calculations. Band structure and total DOS of Co2 FeGe compound was investigated. Thermodynamic properties of Co2 FeGe were investigated within the quasi-harmonic approximation using Gibbs2 code. Seebeck coefficient, electrical conductivity, electronic, thermal conductivity, and figure of merit are studied.